Anti-MuSK-Positive Myasthenia Gravis in a Patient with Parkinsonism and Cognitive Impairment. (31st July 2011) - Lanfranconi, S.; Corti, S.; Baron, P.; Conti, G.; Borellini, L.; Bresolin, N.; Bersano, A.
Abstract : Muscle-specific tyrosine kinase- (MuSK-) antibodies-positive Myasthenia Gravis accounts for about one third of Seronegative Myasthenia Gravis and is clinically characterized by early onset of prominent bulbar, neck, shoulder girdle, and respiratory weakness. The response to medical therapy is generally poor. Here we report a case of late-onset MuSK-antibodies-positive Myasthenia Gravis presenting with signs of cognitive impairment and parkinsonism in addition to bulbar involvement and external ophthalmoplegia. The pattern of involvement of both peripheral and central nervous system dysfunction might suggest a common pathogenic mechanism, involving impaired cholinergic transmission.